Hukum Formal dan Praktik Sosial dalam Mengurai Kesenjangan Upah Gender di Sektor Informal Indonesia - Kinanti Lukman Sari (Media Hukum Indonesia (MHI), 2026)
The gender wage gap in Indonesia's informal sector is a deep-rooted issue that hasn't been properly tackled by law. Though there are many rules like the 1945 Constitution, Law No. 13/2003 on Manpower, Law No. 11/2020 on Job Creation, and international agreements such as CEDAW and ILO Convention No. 100, which all support the idea of equal treatment, women in the informal sector still earn less than men. This study, based on existing research, looks at the challenges women in informal jobs face, the difference between the laws and how they are actually applied, and the long-standing barriers that keep pay inequality alive. The results show that unequal pay isn't just because of poor enforcement of the law, but also because of deep-rooted beliefs that women are not the main earners, their lack of access to money and training, and the fact that there's no official system to check labor conditions in the informal sector. These pay gaps cause serious problems in society and the economy, like more women living in poverty, fewer chances for kids to get an education or good healthcare, and lower overall productivity for the country. Even though the legal system in Indonesia seems strong, it doesn't work well for informal workers because there are no systems in place to reach them. The study calls for a more flexible and community-focused legal strategy, stronger groups of women in the informal sector working together, and a change in how society sees the value of women's work to truly achieve fair pay.